2019
DOI: 10.3390/min9090518
|View full text |Cite
|
Sign up to set email alerts
|

Tectonic Transformation and Metallogenesis of the Yanshan Movement during the Late Jurassic Period: Evidence from Geochemistry and Zircon U-Pb Geochronology of the Adamellites in Xingcheng, Western Liaoning, China

Abstract: The Yanshan Movement occurred mainly during the Middle-Late Jurassic, and gave rise to NE trending structures, magmatic events, volcanism and mineral resources. The transformation and evolution of the movement during the Middle-Late Jurassic were investigated from the rock assemblage, geochemistry, and chronology in adamellites which were exposed in the Xingcheng area, western Liaoning. Two types of adamellites were recognized—biotite adamellites with the formation age of 172–168 Ma and garnet-bearing adamelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 60 publications
(98 reference statements)
0
9
0
Order By: Relevance
“…Trace elements were tested by an inductively coupled plasma mass spectrometer (ICP-MS Agilent 7500ce). Details of the analytical methods are given by Hu et al [60].…”
Section: Major-and Trace-element Analysesmentioning
confidence: 99%
“…Trace elements were tested by an inductively coupled plasma mass spectrometer (ICP-MS Agilent 7500ce). Details of the analytical methods are given by Hu et al [60].…”
Section: Major-and Trace-element Analysesmentioning
confidence: 99%
“…Others suggested that the magmatism formed in an active compressive continental margin, induced by subduction of the Paleo-Pacific Plate beneath eastern China (Cisse et al, 2017;Hu et al, 2019;Shi et al, 2019;Xu et al, 2016;Zhu, Yang, & Wu, 2012).…”
Section: Tectonic Setting and Implications For Metallogenesismentioning
confidence: 99%
“…178 Ma (Jiang et al, 2010;Tang et al, 2018;Xu et al, 2013), indicating that the thickening of the eastern NCC crust during the Middle Jurassic likely resulted from the compression induced by the subduction of the Paleo-Pacific Plate. There is consensus that the northern margin of the NCC underwent tectonic compression during the Jurassic, based on the large-scale thrust faults and folds (Wu et al, 2011) and the intense widespread Jurassic magmatism in the northern margin of the NCC (Dong et al, 2018;Fan et al, 2017;Hu et al, 2019). The northern margin of the NCC underwent extension during the Early Cretaceous, and is characterized by extensional rift basins (Meng, Hu, Jin, Zhang, & Xu, 2003;Ren, Tamaki, Li, & Zhang, 2002;Zhang, Zhao, Dong, & Yang, 2004), extensive detachment, normal faults (Zhang et al, 2004), and metamorphic core complexes (Davis et al, 1998;Wang et al, 2012).…”
Section: Tectonic Setting and Implications For Metallogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…geochemical data indicate that the Kengdenongcuo rhyolitic tuffs, which host the deposit, originated along with contemporaneous syn-collision granitoids in the region due to arc-type magmatism as the Paleo-Tethys Ocean was closed. The contribution of Hu et al [6] concerns biotite adamellites, with the formation age of 172-168 Ma, and garnet-bearing adamellites of 158-152 Ma, which occur in the Xingcheng area of western Liaoning. Geochronologic studies of the ore deposits in western Liaoning show that these Mesozoic metalliferous deposits formed in a compressive environment influenced by the subduction of the Paleo-Pacific plate.…”
mentioning
confidence: 99%